2008
DOI: 10.14227/dt150308p17
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Characterization and Dissolution Study of Solid Dispersions of Furosemide with Polyethylene Glycol 6000 and Polyvinylpyrrolidone K30

Abstract: Solid dispersions traditionally have been used as effective methods to improve the dissolution properties and bioavailability of poorly water-soluble drugs. The aim of the present study was to improve the solubility and dissolution rate of a poorly water-soluble drug, furosemide, by a solid dispersion technique. Solid dispersions were prepared using polyethylene glycol 6000 (PEG 6000) and polyvinylpyrrolidone K30 (PVP K30) in different drug-to-carrier ratios. Dispersions with PEG 6000 were prepared by fusion-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 14 publications
4
33
0
Order By: Relevance
“…The drug also exhibits absorption at 2251 and 3317 cm −1 indicating the exocyclic tricyclic triple bond and the stretching of N-H, respectively[20]. Important vibrations detected in the spectrum of PEG 8000 were the C-H stretching at 2880 cm −1 and the C-O (ether) stretching at 1110 cm −1 [2122]. The spectrum of PVP K30 showed important bands at 1652 cm −1 which indicates C=O stretch in the cyclic amide and a broad band at about 2850-3000 cm −1 attributed to aliphatic C-H stretch.…”
Section: Resultsmentioning
confidence: 99%
“…The drug also exhibits absorption at 2251 and 3317 cm −1 indicating the exocyclic tricyclic triple bond and the stretching of N-H, respectively[20]. Important vibrations detected in the spectrum of PEG 8000 were the C-H stretching at 2880 cm −1 and the C-O (ether) stretching at 1110 cm −1 [2122]. The spectrum of PVP K30 showed important bands at 1652 cm −1 which indicates C=O stretch in the cyclic amide and a broad band at about 2850-3000 cm −1 attributed to aliphatic C-H stretch.…”
Section: Resultsmentioning
confidence: 99%
“…It shows excellent water solubility. Its molecular size (ranging from 10,000 to 700,000) favors the formation of interstitial solid solutions; it has been demonstrated to retard the drug crystallization giving amorphous solid dispersions with increased drug dissolution rates and solubilities (Patel et al 2008). PVP is capable of forming molecular adducts with many compounds; the presence of hydroxyl or carbonyl groups in the repeat units of the polymer tends to increase the water solubility and stability of the drug and also improves its bioavailability (Anant et al 2004).…”
Section: Resultsmentioning
confidence: 99%
“…The more negative values of the entropy (ΔS) indicated the high orderness of complexes in case of all the systems. 12 These values indicated that the system was releasing the energy upon complexation forming a ordered complexes respectively, implying highly stable physical state of all the complexes.…”
Section: Temperatures (1/t) the Values Of Enthalpy (δH)mentioning
confidence: 94%